Claiming Wagner for France : Music and Politics in the Parisian Press, 1933-1944 - Orzech, Rachel (Book collections on Project MUSE., 2022)
"This book examines the shifting attitudes toward Wagner reflected in the Parisian press during the period of the Third Reich. Paradoxically, during one of the darkest periods of French history, as the German threat grew more tangible and then manifested in the Nazi occupation of France, Parisians chose to see in Wagner a universality that transcended his Germanness. As Franco-German diplomatic relations gradually worsened in the 1930s, Wagner became an increasingly integral part of French musical culture. Parisians were unwilling to surrender Wagner to German exclusivist claims. In previous decades the French had used Wagner to symbolize a diverse array of political arguments and positions, from right-wing nationalism to left-wing humanism and egalitarianism, In the 1930s, however, the Parisian press depicted him as a universalist. Although Wagner had stood in for German nationalism and chauvinism in recent periods of Franco-German conflict, in the 1930s Parisians refused this notion and attempted to reclaim his role in their own national history and imagination. Even once war was declared in 1939 and a ban on the performance of Wagner's music was implemented, commentators insisted that it was simply a temporary measure designed to avoid public disturbance. Simultaneously, they maintained that 'music has no borders,' and that 'it is childish to mix art and politics.' The Wagner discourses that emerged from the 1930s Parisian press paved the way for the dominant Wagner discourse in the German-controlled Occupation press: Collaboration through Wagner. By a great irony of history, the concept of Wagner the universalist that had been used to resist the Nazis in the 1930s was transformed into the infamous collaborationist rhetoric promoted by the Vichy government between 1940 and 1944"--